A thermostable glucoamylase from Bispora sp. MEY-1 with stability over a broad pH range and significant starch hydrolysis capacity. - Huifang Hua; Huiying Luo; Yingguo Bai; Kun Wang; Canfang Niu; Huoqing Huang; Pengjun Shi; Caihong Wang; Peilong Yang; Bin Yao (PLoS ONE, 2014)
Background Glucoamylase is an exo-type enzyme that converts starch completely into glucose from the non-reducing ends. To meet the industrial requirements for starch processing, a glucoamylase with excellent thermostability, raw-starch degradation ability and high glucose yield is much needed. In the present study we selected the excellent Carbohydrate-Activity Enzyme (CAZyme) producer, Bispora sp. MEY-1, as the microbial source for glucoamylase gene exploitation. Methodology/principal findings A glucoamylase gene (gla15) was cloned from Bispora sp. MEY-1 and successfully expressed in Pichia pastoris with a high yield of 34.1 U/ml. Deduced GLA15 exhibits the highest identity of 64.2% to the glucoamylase from Talaromyces (Rasamsonia) emersonii. Purified recombinant GLA15 was thermophilic and showed the maximum activity at 70°C. The enzyme was stable over a broad pH range (2.2-11.0) and at high temperature up to 70°C. It hydrolyzed the breakages of both α-1,4- and α-1,6-glycosidic linkages in amylopectin, soluble starch, amylose, and maltooligosaccharides, and had capacity to degrade raw starch. TLC and H1-NMR analysis showed that GLA15 is a typical glucoamylase of GH family 15 that releases glucose units from the non-reducing ends of α-glucans. The combination of Bacillus licheniformis amylase and GLA15 hydrolyzed 96.14% of gelatinized maize starch after 6 h incubation, which was about 9% higher than that of the combination with a commercial glucoamylase from Aspergillus niger. Conclusion/significance GLA15 has a broad pH stability range, high-temperature thermostability, high starch hydrolysis capacity and high expression yield. In comparison with the commercial glucoamylase from A. niger, GLA15 represents a better candidate for application in the food industry including production of glucose, glucose syrups, and high-fructose corn syrups.